Tinjauan Yuridis Terhadap Akibat Tidak Melaksanakan Putusan Pengadilan Agama Terkait Pemberian Nafkah Pasca Cerai: Analisis Putusan Perkara No. 2569/Pdt.G/2022/PA.Gs - Fauziyah Rohmawati (MASADIR: Jurnal Hukum Islam, 2023)
This research was motivated by the fact that quite a few parents neglected their responsibilities and obligations to their children after divorce, to the point that their children became neglected. This study will examine the court decision regarding post-divorce maintenance in case no. 2569/Pdt.G/2022/PA.Gs, a judicial review of the consequences of not implementing the court decision regarding post-divorce maintenance in case no. 2569/Pdt.G/2022/PA.Gs. as well as legal measures that can be taken by the wife and children in case No. 2569/Pdt.G/2022/PA.Gs. The methodology used in writing this scientific work is library research. The type of research is normative using a case approach. The research results show that Decision No. 2569/Pdt.G/2022/PA. Gs The implementation of the contents of the decision was not carried out properly. The consequences for not paying child support include child neglect (articles 76 and 77 of Law No. 35 of 2014) which carries a maximum penalty of imprisonment for 5 (five) years and/or a maximum fine of IDR 100,000,000. 00 (one hundred million rupiah). So the legal action that can be taken by the ex-wife is to submit a forced effort to the court against the ex-husband to provide maintenance, which is called a request for execution of the decision. The legal instrument used in the decision is Article 195-197 HIR, providing legitimacy to parties who feel their rights in the household have been violated to demand justice